PERENCANAAN STRATEGIS SISTEM INFORMASI DAN TEKNOLOGI INFORMASI UNTUK MENINGKATKAN DAYA SAING SEKOLAH PADA SMA ISLAM AL-FALAH JAMBI - Akbar, Zulfikri; Kurniawansyah, Kevin; Rohayani, Hetty; Yaakub, Saleh (LPPM Universitas Muhammadiyah Jambi, 2023)
According to data recorded at the end of the even semester of the 2019/2020 academic year, Al-Falah Jambi Islamic High School currently has 403 active students, 39 permanent foundation teachers, and 7 foundation contract teachers. With the increasing number of active students, which can be seen from the number of students at the beginning of its establishment, which amounted to 85 students, the services that must be provided and the academic atmosphere must remain conducive and maintained. Therefore, an information system strategic plan is needed that supports the school's business strategy and is aligned with the school's vision, mission, and goals to be able to advance Al-Falah Jambi Islamic High School and increase competitive advantage with other private SMA/SMK or with public SMA/SMK existing or future. The data collection technique that the writer used in this study was by means of interviews, observation, literature study, and documentation. The analytical methods used include the Value Chain Analysis, PEST Analysis, Porter's Five Forces, SWOT Analysis, Balanced Scorecard Analysis, the Critical Success Factor (CSF) Analysis, Gap Analysis, and McFarlan Strategic Grid Analysis. The targeted output of this research is to produce recommendations for an IS/IT strategic plan aimed at all parties, both the Principals, TU Heads, and ICT divisions, and can obtain future information system proposals and be mapped in development plans within a five-year period and mapped based on user units, namely HR, leadership, corporate secretary, treasurer, curriculum, inventory, and ICT, so that Al-Falah Jambi Islamic High School can increase competitive advantage with other private SMA/SMK or with existing or future public SMA/SMK